The effect of the talking stick method on improving students’ learning outcomes in islamic religious education at SMPN Satap 2 Tinondo - Fajriani, Najma; Nurhayati, Nurhayati; Aulia, Andi Nurul (Educenter : Jurnal Ilmiah Pendidikan, 2025)
Education is a very important activity in preparing children to face their future lives. In fact, the phenomenon of the educational process has existed since the beginning of human life, although its implementation was still very simple in the early stages. This study aims to determine the effect of the Talking Stick learning method on the Islamic Religious Education learning outcomes of eighth-grade students at SMPN Satap 2 Tinondo. This research employed a quantitative approach using an experimental method. The study sample consisted of 50 students selected from the entire eighth-grade population. The instrument used was a questionnaire that had undergone validity and reliability testing. Data analysis was carried out through normality, homogeneity, linearity, and t-tests. The results of this study indicate that the Talking Stick method has a significant effect on learning outcomes. However, field observations show that the success of learning is not solely determined by the method, but also by students’ readiness, activeness in discussions, and teacher support. Therefore, the Talking Stick method has a positive and significant effect, but its effectiveness can be optimized if supported by other collaborative and consistent learning strategies.